Qualities of Physician in Light of Charaka Samhita - A Literary Study - Majumder, Bijita; Ray, Sukalyan (International Research Journal of Ayurveda & Yoga, 2022)
In Ayurveda, among the four limbs of healthcare system, physician is considered as the most important and principal among others. A successful health care service is primarily dependent on the proficiency of a physician having all the necessary qualities as mentioned in the ancient compendiums. Charaka Samhita being the most important text among all the resources of Ayurveda has given much emphasis on the various aspects of a Bhishaka or Vaidya (physician) - right from his basic qualities, advanced qualities, ideal role in healthcare service, his character and so many other things. Along with these aspects, this compendium also has elaborate description about various categories of physician - both ideal ones and the counterfeits. Along with health care system, as an essential tool for medical education, Charaka Samhita has also discussed the various aspects of an ideal teacher - his qualities, character and duties - which are essential for making a person a competent physician. All this ancient knowledge will help us to understand better about the ideal character of a physician as it should be in today’s society.